Peran Orang Tua Tunggal (Bapak Atau Ibu) Dalam Mendidik Dan Mengasuh Anak Di Kelurahan Gondrong - Azmelia Putri Balqis; Mochamad Naim; Rizki Setiawan (Peneliti.net, 2023)
This study uses a qualitative and descriptive approach to research, the end results of which provide detailed insights. Primary and secondary data sources used were interviews with researchers, and data were evaluated using a descriptive analysis approach. In research, role theory is taken as the theoretical basis. The findings of this study concern the role of single parents in raising their children on Jl Blok American I Gondrong Village. Children raised in democratic parenting are more responsible, warm and independent. Children raised in permissive parenting are less responsible and less rebellious. A child with an authoritarian parenting style is more stressed, but lacks a sense of responsibility.